Endoscopic Treatment of GERD in Patients With Obesity. Issue 4 (December 2021) - Ghazi, Rabih; Rapaka, Babusai; Abu Dayyeh, Barham K.
Gastroesophageal reflux disease (GERD) is one of the most common obesity-associated comorbidities. The increasing prevalence of obesity worldwide is expected to cause a concomitant increase in the prevalence of GERD. While laparoscopic Nissen fundoplication (LNF) remains the gold standard for the treatment of GERD, its efficacy in the setting of obesity is limited by a relatively high rate of post-procedural reflux recurrence. Currently, Roux-en-Y gastric bypass (RYGB) is the gold standard treatment for GERD in patients with obesity. However, despite its proven efficacy, it remains underutilized due to its cost, safety concerns, and patient acceptance. During the past 2 decades, endoscopic therapies have emerged as minimally invasive and safe alternatives for the management of GERD. While most studies assessed their outcomes in patients without obesity, recently published case reports offered a potential framework for their use in patients with obesity. In this article, we review the available endoscopic anti-reflux therapies (EART) and endoscopic bariatric therapies (EBT), with emphasis on their potential role in the management of GERD in patients with obesity.